Developing a Mentorship Program in Laos - Helen Nita Catton (Frontiers Media S.A., 2017)
Skills strengthening and capacity building for maternal and newborn health (MNH) providers are essential to ensure quality care for mothers and newborns. There is, however, limited research regarding what constitutes an effective model in low-income countries. The Lao People's Democratic Republic (Laos) has some of the region's worst outcomes for neonatal and maternal mortality. Moreover, with a 23-year hiatus in midwifery training, which ended approximately 7 years ago, there is a cadre of new and inexperienced midwives in practice without support systems, skills, or continuing professional development opportunities. Traditional didactic teaching methodologies prevail in Laos, but with little evidence of efficacy. As an alternative model, Save the Children International has been implementing a mentorship approach for MNH providers in two provinces in northern Laos since January 2016, with technical guidance and funding from the United States Agency for International Development-supported global Maternal Child Survival Program. This community case study will describe and reflect on the approach by highlighting the need and rationale for mentorship, followed by a description of the program's core components and the results observed so far. Lessons learned and the application of the approach to different contexts and health-care professionals, considering both constraints and opportunities, will be discussed.